2022
DOI: 10.1017/gmh.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 post-vaccination depression in older Israeli adults: the role of negative world assumptions

Abstract: Background: With the outbreak of SARS-CoV-2 pandemic, the aging population has been shown to be highly vulnerable. As a result, policy makers and the media urged older adults to restrict social interactions, placing them at greater risk of mental health problems, such as depression. However, there has been little previous attempt to examine COVID-19 vaccine related risk factors and depressive symptoms amongst older adults. Methods: Participants (938 older adults, Mage=68.99, SD=3.41, range 65-85) answered an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Additionally, our results suggest that in comparison with those suffering from CPTSD with those who do not reach the PTSD cutoff level, married older adults reported higher levels of CPTSD. This finding was unexpected as previous research focusing on the benefits of marriage reported links between marriage with better mental health, including higher life satisfaction (Fu and Noguchi, 2016) and lower depression and anxiety (Purba and Fitriana, 2019). Nonetheless, the current findings may be understood in light of the pandemic era, whereby researchers questioned whether being married served as a buffer to the stresses and policies foisted by COVID-19 (Purba et al, 2021), as fear, worry, and fundamental existential survival became paramount, which may result in the loss of the essential support provided by marital bonding (Maiti et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, our results suggest that in comparison with those suffering from CPTSD with those who do not reach the PTSD cutoff level, married older adults reported higher levels of CPTSD. This finding was unexpected as previous research focusing on the benefits of marriage reported links between marriage with better mental health, including higher life satisfaction (Fu and Noguchi, 2016) and lower depression and anxiety (Purba and Fitriana, 2019). Nonetheless, the current findings may be understood in light of the pandemic era, whereby researchers questioned whether being married served as a buffer to the stresses and policies foisted by COVID-19 (Purba et al, 2021), as fear, worry, and fundamental existential survival became paramount, which may result in the loss of the essential support provided by marital bonding (Maiti et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
“…Older adults need to be encouraged/supported for increased physical activity and social engagements for their physical and mental health benefits. Studies of older adults in Brazil and Israel showed that depressive symptoms increased or still prevailed even after getting vaccinated ( Greenblatt-Kimron et al, 2022 ; Vidal Bravalhieri et al, 2022 ). Increased physical activity might also be an effective strategy for boosting antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…Links were reported between the COVID-19 pandemic and depression among older adults [ 2 ]. Older age was established as a threat for COVID-19 complications [ 2 ], with studies during the pandemic showing that older adults displayed depressive symptoms, anxiety [ 5 ], peritraumatic distress [ 6 ], post-traumatic stress disorder [ 7 ], and depression even after receiving the vaccination [ 8 ]. Moreover, a link was found between loneliness with depressed mood and increased use of antidepressant medication among older adults during the first COVID-19 lockdown in the UK [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms are perilous to older adults’ overall health [ 4 ], with studies reporting links between the COVID-19 pandemic and depression in older adults [ 2 ]. Beck’s [ 11 ] cognitive developmental model of depression proposes that depressive symptoms embody negative interpretations of life events as demonstrated during the pandemic, with a relationship found between older adults holding negative world assumptions and a 4.4 times higher probability for clinical depressive symptoms than those with positive world assumptions [ 8 ]. Of particular significance to the current study, psychosocial resources, namely optimism and social support, were found to buffer depression among older adults during the pandemic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%